The incidence of autonomous learning on learning english as a foreign language: case of Advanced Intensive English I of the Bachelor of Arts in English with emphasis in Teaching at the Department of Foreign Languages of the University of El Salvador in the year 2015. - Campos Villafuerte, Jairo Wilfredo
Autonomous Learning has become a useful part in the learning process; it is always related to a new language that is tried to be learnt. One of the tools to learn a new language is Autonomy on what the person does; however, the guidance of someone is required somehow. The history of Autonomy is based on what some writers have said and their influences to Autonomous Learning in English Learning; indeed the first publications about the beginnings of Autonomous Learning were at least 30-year in history, and the concept has been some kind of ‘mainstream’ for a long period of time. According to Henri Holec(1979), and Oskarsson(1980) “the earliest publications were mainly French in origin and then the concept was translated to Spanish version, and/or associated with the Council of Europe”, and they continued saying “there was an early strand of work in the field of ‘individualisation’ because some writers wanted to be part of the concept by themselves; in the UK (Altman and James 1980,Geddes and Sturtridge 1988) which was later to join up with autonomy.” Indeed, the very first publication on the list was an Anglo-French collaboration; giving the concept that later was omitted by another writer said Harding-Esch (1977) Researchers present a list of chronological events that are attached to Autonomous Learning and the progress this topic has had during the last three decades. There is a website that provides a concept of learner autonomy and where it was first introduced in 1979 with the study of language and its contribution to autonomy, it says “Autonomy is an acclimatizing skill that allows learners to build up supportive structures within themselves rather than to have a wrong concept about to be independent in study.” The website also includes ideas from other writers: “Autonomy is a faculty for disconnection, crucial consideration, decision-making and self-regulating action (Little, 1990); the condition where an individual is completely responsible for all the choices concerned with his learning and the process involved in carrying out those decisions (Dickinson, 1993); the willingness to take control of an individual’s own learning based on his own needs and purposes (Dam, 1995). The term "learner autonomy" was first coined in 1981 by Henri Holec, the "father" of learner autonomy. Moreover definitions have since been given to the term, depending on the writer, the context, and the level of debate educators have come to. Learner Autonomy is whether researchers view it as a means to an end (learning a foreign language) or as an end in itself (making people autonomous learners).